Persons’ self-improvement as an integrated self-determined phenomenon - Serdiuk, Liudmyla; Penkova, Olena (Social Welfare: Interdisciplinary Approach, 2015)
The article discusses psychological principles of integrated organization of a self-improvement phenomenon. It was determined that self-improvement as a self-determined phenomenon is conditioned and mediated by a set of interconnected personal characteristics, including the value of self-development, integrity of life course perception, self-acceptance and so on. The article reveals structural characteristics of self-improvement as a self-determined system, the basic parameters of which include the value of self-improvement, self-efficacy and personal autonomy. Expediency was justified of an integrated study of objective laws of a self-improvement process through personal and value-semantic mediation. An important factor of self-improvement is a need for self-fulfilment that actualizes person’s potential abilities, supports internal state of tension, is the source of activity and self-activity, has a social character (social status achieving), can be formed purposefully during mastering of any activity.